A new mean‐field plasma edge transport model based on turbulent kinetic energy and enstrophy. Issue 5 (13th January 2020) - Coosemans, Reinart; Dekeyser, Wouter; Baelmans, Martine
Abstract: The predictive capabilities of mean‐field plasma edge transport codes are significantly reduced by the empirically determined radial diffusion coefficients commonly used to account for the turbulent transport. This paper aims to assess a two‐equation model including both turbulent kinetic energy and turbulent enstrophy for an improved description of the mean‐field turbulent transport. A turbulent enstrophy equation is analytically derived for isothermal, electrostatic, two‐dimensional, interchange‐dominated ExB turbulence in the scrape‐off layer. Evaluation of this equation shows that interchange is the dominant source, while the sheath loss and viscous terms provide the main sinks of turbulent enstrophy. Transport effects turn out to be of minor importance. A model for the combined turbulent kinetic energy and enstrophy equations and the particle transport is constructed starting from a one‐equation model for the turbulent kinetic energy. The resulting two‐equation model is shown to retain the dominant dynamics of the latter while improving its scalings.